How far the zone of heat-induced transient block extends beyond the lesion during RF catheter cardiac ablation - Juan J. Pérez; Enrique Berjano; Ana González-Suárez (International Journal of Hyperthermia, 2023)
AbstractPurpose While radiofrequency catheter ablation (RFCA) creates a lesion consisting of the tissue points subjected to lethal heating, the sublethal heating (SH) undergone by the surrounding tissue can cause transient electrophysiological block. The size of the zone of heat-induced transient block (HiTB) has not been quantified to date. Our objective was to use computer modeling to provide an initial estimate.Methods and materials We used previous experimental data together with the Arrhenius damage index (Ω) to fix the Ω values that delineate this zone: a lower limit of 0.1–0.4 and upper limit of 1.0 (lesion boundary). An RFCA computer model was used with different power-duration settings, catheter positions and electrode insertion depths, together with dispersion of the tissue’s electrical and thermal characteristics.Results The HiTB zone extends in depth to a minimum and maximum distance of 0.5 mm and 2 mm beyond the lesion limit, respectively, while its maximum width varies with the energy delivered, extending to a minimum of 0.6 mm and a maximum of 2.5 mm beyond the lesion, reaching 3.5 mm when high energy settings are used (25 W–20s, 500 J). The dispersion of the tissue’s thermal and electrical characteristics affects the size of the HiTB zone by ±0.3 mm in depth and ±0.5 mm in maximum width.Conclusions Our results suggest that the size of the zone of heat-induced transient block during RFCA could extend beyond the lesion limit by a maximum of 2 mm in depth and approximately 2.5 mm in width.